Role of Damsisa and Synbiotics in Treatment of Unthriftiness in Buffalo Calves in Sharkia Governorate - Ismail, Eman I.M.; Darwish, Mohamed E.; El said, Halla A.; Kalill, Halla M.; Mabrouk, Marwa; Salama, Amany M. (Journal of Advanced Veterinary Research, 2023)
Unthriftiness is the major problems affect health and body performance of calves and induce many losses even with treatment. So, the aim of the present study was to investigate some adverse effects of unthriftiness on hematobiochemical parameters and some antioxidant enzymes as well as using Ambrosia maritime or synbiotics each alone with mineral mixture in treatment unthrifty calves. A total of 20 buffalo calves of 4-6 month old (5 healthy calves and their body weight 200-250 kg, in addition to 15 unthrifty calves and their body weight 120-150 kg) belonged to a private farm in Abo Hamad City - Sharkia Province. All calves were injected with one dose of Ivomec super to ensure that all calves were free from internal and external parasite. At day 30 post Ivomec injection, calves were divided into 4 equal groups (5/each). All calves were received 3 kg concentrates contain 2 kg mineral mixture/ton and 5 kg berseem all over the experimental period. The1st group healthy buffalo calves (-ve control), the 2nd group unthrifty calves not treated (+ve control), the 3rd group unthrifty calves received 0.5 ml synbiotics /I liter drinking water for 60 successive days, the 4th group unthrifty calves received 1 % dried leaves of damsisa for 60 days. All caves were weighted at start of the experiment and at 1st day post treatment for determination weight gain and FCR. At1st day post treatment blood samples were taken from all calves for estimation some hematobiochemical parameters. Unthrifty calves show significant decrease in serum copper, iron, selenium, zinc, body weight gain, RBCs, Hb, PCV, WBCs, serum total protein albumin, globulin, A/G ratio cholesterol, CAT and SOD beside insignificant decrease in Ca, Ph, Na, FCR, total lipid, triglycerides and MDA associated with non-significant increase in AST, ALT, ALP. Findings revealed that unthrifty calves received synbiotics Â or damsisa for 60 successive days displayed significant increases in weight gain, total protein, albumin, globulin, A/G ratio, beside insignificant increases in copper, iron, selenium, zinc, Ca, Ph, Na, RBCs, Hb, PCV, WBCs, AST, ALT, ALP, Total lipid, triglyceride, MDA coupled with non-significant decreases in RBCs, Hb, PCV and WBCs, serum cholesterol, CAT and SOD. It could be concluded that unthriftiness induce many adverse effects in health and body performance of calves but mineral mixture with synbiotics or with damsisa had better results in improvement the adverse effects in hematobiochemical parameter in unthrifty calves.